Effects of future climate change on the preservation of artworks, thermal comfort and energy consumption in historic buildings - Muñoz-González, Carmen María; León-Rodríguez, Ángel Luís; Suárez Medina, Rafael C.; Ruiz-Jaramillo, Jonathan (Elsevier, 2020)
Climate change will affect the indoor temperature of historic buildings, impacting the preservation of artworks and the thermal comfort of users, and possibly leading to increased energy consumption. These buildings generate more emissions than new buildings and in most European countries, preservation principles take precedence over energy efficiency and the reduction of emissions. This research is a key topic for the mitigation of climate change and proposes a method for assessing the impact of climate change on the preservation of artworks, thermal comfort, and energy consumption. An experimental method was followed, combining analytical formulations, on-site measure ments, and Heating, Ventilation and Air Conditioning systems in order to identify the adequate hygrothermal parameters for historic buildings. The climate change scenario predicted for 2050 was based on projected tem perature variation. The case studies were Baroque churches, historic buildings located in the south of Europe. Data obtained from a monitoring campaign carried out in these churches was used to validate dynamic simulation models. The churches analysed showed an increase in cooling demand and a decrease in heating demand. Furthermore, in order to ensure human comfort and the preservation of artworks, it was necessary to implement active systems in operation for 12-hour periods. These results suggest an energy overconsumption, as the energy consumption for human comfort and artwork preservation was 50% higher than the energy consumption of active systems for the preservation of valuable historic objects. In addition, the annual energy consumption decreases for future scenarios for 2050 in the case of artwork preservation and thermal comfort, but increases by almost 15% for the preservation of works of art due to higher level relative humidity. Before historic buildings can be adapted.
Keywords: Edificios históricos - Conservación y restauración; Climate Change; Heritage; Artwork; Preservation; Simulation; Thermal comfort